(untitled) (City: History, Culture, Society, 2023)
The publication examines the spread of the “stummel”-shaped smoking pipe in the Ukrainian territory of the Russian Empire from the end of the eighteenth century to the beginning of the nineteenth century. Prior to the advent of cigarettes in the 20th century, these pipes were widely used. The inclusion of archaeological and ethnographic sources made it possible to establish the manufacturing 221 technology of metal accessories for these pipes and to clarify the names of their structural compo - nents. Publication of an ethnographic source — a photograph and transcription of a manuscript from the expedition of the famous archaeologist, ethnographer, and ceramologist of the late 19th and early 20th centuries — Ivan Antonovych Zaretskyi — dedicated to the making of a wooden cradle with met - al accessories and a decorative lid. The music was composed by Luka Meleshko of the village of Vely - ka Pavlivka in the Zinkivsky district of the Poltava region. He drew a pipe with a lid and stem attached and signed the names of the product’s components. The study involved the metal components of 19 wooden pipe fragments discovered during archaeo - logical excavations in the Poltava region, primarily in the regimental city of Poltava. The authors ana - lyzed the manufacturing technology of metal pipe components. On the basis of stratigraphic obser - vations and European analogies, it has been determined that these pipes were used between the late 18th and early 19th centuries. In general, it can be assumed that clay pipes predominated in quantity on the territory of sub-Russian Ukraine from the 17th to the end of the 18th century. Porcelain and earthenware pipes imported from Europe were among the elite, but they were not widely used. In the 1830s, there was a sharp decline in the number of clay smoking devices, while wooden pipes became increasingly popular. Beginning at the end of the 18th century and particularly in the first quarter of the 19th century, wooden pipes in the form of “stummels” became popular, first among the military and then the general populace. These inexpensive items, with their simple-to-use, low-art accessories, became a distinguishing characteristic of the military environment and, later, of the poor populace. General stratigraphic archaeological observations confirm this. Particularly, the materials from Polta - va indicate that similar products were popular among the residents of Poltava as early as the late 18th century, and that the end of the 1930s can be considered the height of the new fashion for these items in the city. With the expansion of the source base, this date may be subject to change. Over the vast expanse of Ukrainian territory, a certain similarity can be observed in the manufactur - ing process and the names of smoking accessories’ components. During the late 19th and early 20th centuries, artisanal production made use of the centuries-old know-how for crafting individual com - ponents, particularly lids.